Antimicrobial mouthwashes (gargling) and nasal sprays to protect healthcare workers when undertaking aerosol‐generating procedures (AGPs) on patients without suspected or confirmed COVID‐19 infection - Burton, M; Clarkson, JE; Goulao, B; Glenny, A-M; McBain, AJ; Schilder, AGM; Webster, KE; Worthington, HV (Cochrane Collaboration, 2020)
Background: COVID‐19 infection poses a serious risk to patients and – due to its contagious nature – to those healthcare workers (HCWs) treating them. The risks of transmission of infection are greater when a patient is undergoing an aerosol‐generating procedure (AGP). Not all those with COVID‐19 infection are symptomatic, or suspected of harbouring the infection. If a patient who is not known to have or suspected of having COVID‐19 infection is to undergo an AGP, it would nonetheless be sensible to minimise the risk to those HCWs treating them.